The association between type 2 diabetes and pulmonary cavitation revealed among IGRA-positive tuberculosis patients - Yang, Min; Li, Pei; Liu, Han; Zhu, Xiaojie; Zhu, Guofeng; Zhang, Peize; Deng, Guofang (Frontiers in Medicine, 2023)
The co-occurrence of tuberculosis (TB) and diabetes mellitus (DM) presents a significant obstacle to TB eradication. Pulmonary cavitation can occur in severe cases of TB, particularly in patients with DM. We conducted a cross-sectional study of 1658 smear-or culture-confirmed pulmonary TB (PTB) patients participating in the Second Department of Pulmonary Medicine and Tuberculosis, Shenzhen, China, from 1 May 2014 through 30 June 2019. A final of 861 participants which satisfied the criteria (chest CT scan for cavitation, interferon gamma release assay (IGRA), diabetes mellitus diagnosis), with the median age of 36.7 years, 63.6% of male, IGRA positive was 79.7%, 13.8% had diabetes and 40.8% had pulmonary cavitation, were conducted study. The association between diabetes and pulmonary cavitation was confirmed in these TB patients (adjusted OR, 2.54; 95% CI, 1.66-3.94; p<0.001). Neither association between diabetes and IGRA, nor association between lung cavitary and IGRA was observed. Based on the criteria of IGRA+/-, pulmonary cavitation+/-and DM+/-, the further analysis with univariate and multivariate logistic regression were conducted in 6 subgroups. The significant association between diabetes and pulmonary cavitation was further confirmed in the IGRA+ subgroup (adjusted OR, 3.07; 95% CI, 1.86-5.16; p<0.001), but not observed in IGRA-individuals. This observation suggests that different immunological mechanisms of pulmonary cavitary/DM may be employed in IGRA+ TB patients from IGRA-TB patients.